2016
DOI: 10.3390/genes7100073
|View full text |Cite
|
Sign up to set email alerts
|

Association of XPC Gene Polymorphisms with Colorectal Cancer Risk in a Southern Chinese Population: A Case-Control Study and Meta-Analysis

Abstract: Xeroderma pigmentosum group C (XPC) is a key component of the nucleotide excision repair (NER) pathway. Dysfunctional XPC protein may impair NER-mediated DNA repair capacity and further lead to genomic instability and carcinogenesis. Two common nonsynonymous polymorphisms in the XPC gene, Lys939Gln (rs2228001 A > C) and Ala499Val (rs2228000 C > T), have been investigated in various types of cancer. We genotyped these two polymorphisms in 1141 cases with histologically confirmed colorectal cancer (CRC) and 1173… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 40 publications
0
22
0
Order By: Relevance
“…So far, genome‐wide association studies have reported ~100 risk loci for CRC highlighting new genes and pathways contributing to CRC susceptibility and suggesting roles for Hedgehog signaling, Krüppel‐like factors, Hippo‐YAP signaling, and immune function . Hua et al have also suggested that polymorphisms within xeroderma pigmentosum group C (XPC) and G (XPG) genes may affect CRC susceptibility through impairment of the nucleotide excision repair (NER) pathway …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…So far, genome‐wide association studies have reported ~100 risk loci for CRC highlighting new genes and pathways contributing to CRC susceptibility and suggesting roles for Hedgehog signaling, Krüppel‐like factors, Hippo‐YAP signaling, and immune function . Hua et al have also suggested that polymorphisms within xeroderma pigmentosum group C (XPC) and G (XPG) genes may affect CRC susceptibility through impairment of the nucleotide excision repair (NER) pathway …”
Section: Introductionmentioning
confidence: 99%
“…4,5 Hua et al have also suggested that polymorphisms within xeroderma pigmentosum group C (XPC) and G (XPG) genes may affect CRC susceptibility through impairment of the nucleotide excision repair (NER) pathway. 6,7 Moreover, chronic intestinal inflammation has long been recognized as a prominent CRC driver. 8 Patients affected by inflammatory bowel diseases (IBD), such as Crohn's disease or ulcerative colitis, have been reported to have an increased risk of CRC development.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast with a meta-analysis that studied 679 cases of several types of cancer and 902 controls, the most prevalent allele was A with 0.62 [38], coinciding the allele frequency of the studied population. In a meta-analysis made in a Chinese population, the Lys939Gln polymorphism was significantly associated with the risk of CRC in the A/C heterozygous pattern (OR = 1.40, CI of 95% = 1.16-1.69; p < 0.05) [39]. Another research demonstrated that the patients with the C/C genotype have 2.09 times more risk of developing bladder cancer than normal A/A genotype [40].…”
Section: Discussionmentioning
confidence: 98%
“…A TIANamp Blood DNA Kit (Centrifugal column, Tiangen) was used to extract DNA from the blood samples according to the manufacturer's instructions . TaqMan real‐time PCR assays were set up in 384‐well plates containing positive and negative samples and were carried out in an ABI Q6 system (Applied Biosystems) to genotype the miRNA‐149 rs2292832 T>C polymorphism …”
Section: Methodsmentioning
confidence: 99%